Estudo do perfil oxidativo e atividade da enzima acetilcolinesterase em pacientes com leucemia linfoblástica aguda (lla) - Battisti, Vanessa (2008)
Acute lymphoblastic leukemia (ALL) is the most common cancer found in the pediatric population and is characterized by uncontrolled proliferation and maturation arrest of lymphoid progenitor cells (lymphoblasts) in the bone marrow. In ALL occurs an increase in the production of reactive species and studies show the involvement of oxidative stress in ALL pathogenesis. Moreover acetylcholinesterase (AChE) present in blood and plasma and also in lymphocytes is well established as having non-cholinergic functions including development of cancer and its contribution to the regulation of immune function. Considering such statements, it was investigated the oxidative profile and ACHE activity in ALL patients. Eighty two ALL patients and 50 healthy subjects participated in this study. Patients were divided into 4 groups: newly diagnosed (ND) remission induction (RI), remission maintenance (RM) and out-of-treatment (OT). For evaluation of the oxidative profile, we determined the catalase (CAT) and superoxide dismutase (SOD) activities in blood, thiols non protein (NPSH) in plasma and erythrocytes, as well as, vitamin E, TBARS and protein carbonyl content from serum samples. Damage markers in lipids and proteins, represented by MDA levels and protein carbonylation content respectively, showed increased levels in patients when compared with the control group. In relation to enzymatic defense, represented by the enzymes SOD and CAT, it was observed a decrease in the activities in ALL patients in groups RD, RI and RM, coming back to the normal in OT group. Non enzymatic defense (NPSH in plasma and vitamin E) analyzed also revealed decrease in ALL patients in relation to the controls. No significant difference in NPSH levels was observed between RD group and control group. In relation to AChE activity, in both total blood and lymphocytes, was observed an increase in the RD group in relation to the other groups. On the other hand, in RI and RM the enzyme activity was diminished in relation to control group. No significant difference was observed in AChE activity between FT group and the control group. The results suggest that in ALL an excessive accumulation of reactive species contributes to an antioxidant depletion and dysfunction. The results had also disclosed that the AChE activity is modified in ALL, what can suggest the involvement of this enzyme in the modulation of immune function and in cancer development. The ALL results in a systemic disorder that induces changes, which can be detected by mesuring the peripheral markers of oxidative stress and AChE activity in whole blood and lymphocytes.